Preparation and Characterization of Fruit Smoothies Supplemented with Sissoo Spinach - Md. Nizam, Nurelysha Eriena; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
Obesity is a growing concern in Malaysia, with the 2023 National Health Morbidity Study reporting that 50.1% of Malaysians are overweight or obese. Poor dietary habits, including insufficient consumption of fruits and vegetables, contribute significantly to this issue. To address this, a banana smoothie supplemented with sissoo spinach was developed as a healthy, nutritious, and appealing alternative for individuals seeking a balanced diet. This study also aimed to determine the physicochemical characteristics, nutritional composition, and sensory evaluation of the produced smoothies. The physicochemical analysis involved evaluating parameters such as colour, pH, total soluble solids (TSS), and moisture content. Nutritional composition was determined by analysing protein, dietary fiber, fat, ash, and carbohydrate content. A sensory evaluation was conducted with 50 panellists to assess the acceptability of the smoothies in terms of appearance, taste, aftertaste, aroma, texture, and overall acceptance. The findings revealed that adding sissoo spinach, honey, and lemon influenced the physicochemical properties, resulting in reduced lightness (L*) (37.27 ± 1.33) and pH (5.21 ± 0.01) while maintaining an acceptable TSS level (14.98 ± 0.39 oBrix). Nutritional analysis showed that Formulation 3 had the highest protein (1.59 ± 0.02%) and ash content (0.96 ± 0.02%), indicating improved nutritional value. However, the sensory evaluation demonstrated that Formulation 1 was the most acceptable sample (6.18 ± 1.57), scoring well for appearance (6.32 ± 1.76) and texture (6.42 ± 1.57) while balancing nutritional quality and taste. Finally, the banana smoothie supplemented with sissoo spinach is a promising option for promoting the consumption of dark green vegetables and fruits, particularly among individuals who are reluctant to consume vegetables due to their bitter taste. The incorporation of honey and lemon effectively masked the bitterness, making the smoothie a palatable, convenient, and nutrient-dense choice.